The American Chiropractic Board of Sports Physicians Position Statement on Pre-Participation Examinations: An Expert Consensus - Moreau, William J. (J Chiropr Med, 2015)
OBJECTIVE: The purpose of this paper is to present a position statement of best practices for the provision of a safe and high-quality pre-participation examination (PPE) and to provide recommendations on education requirements for doctors of chiropractic providing the PPE. METHODS: In 2014, the American Chiropractic Board of Sports Physicians (ACBSP) Board of Directors identified a need to review and update the ACBSP position statements and practice guidelines in order to be current with evolving best practices. Twelve ACBSP certificants, 10 Diplomates of the ACBSP, and 2 Certified Chiropractic Sports Physicians, met in April 2015 to author a pre-participation position statement using an expert consensus process. Panel members excluded anyone with commercial conflicts of interest and included individuals with expertise in clinical sports medicine and the performance of PPEs. A literature review was performed and circulated in advance for use by the panel in addressing the topic. The position statement was written through a consensus process and accepted by the ACBSP Board of Directors in May of 2015. RESULTS: The ACBSP Position Statement on Pre-participation Examinations identifies the qualifications and best practices for doctors of chiropractic to perform a PPE. CONCLUSION: This position statement states that doctors of chiropractic with post graduate education and current Diplomates of the ACBSP or Certified Chiropractic Sports Physicians certification have the prerequisite education and qualifying skills to perform PPEs.